Qualitative AnalysisOf European Football Spirits Used For Reforming The Cultivation ConceptOf Chinese TeenageFootball Players - Chen, Yanying; Dai, Shuchang (The journal of contemporary issues in business and government, 2021)
Accommodative glocalization indicates that, the practices, institutions and meanings of glocalized football culture have been pragmatically absorbed (Robertson, 2007). This study is designed to explore the elements of European football being accepted in China and examine how the cultivation concept for Chinese teenage football players has been reformed through learning from Europe in the context of accommodative glocalization. Ethnographic research (participation observation and semi-structured interview) revealed that, Chinese football clubs should avoid conflicts between Chinese local football players and foreign football players being professionally cultivated in Europe. It is of significance to cultivate Chinese teenage football players to learn about European football spirits (not yielding, being progressive and stay in good athletic condition, self-transcendence, collective cooperation), rather than simply pursuing good results in Chinese Super League and depending on European football players’ contributions introduced by clubs. The processes of accommodative glocalization can help to reconsider the advantages and drawbacks of glocalized football culture and reformulate the local football culture in China by absorbing the advantages of glocalized football culture.